Monitoring of sixteen fragrance allergens and two polycyclic musks in wastewater treatment plants by solid phase microextraction coupled to gas chromatography. (January 2015) - Godayol, Anna; Besalú, Emili; Anticó, Enriqueta; Sanchez, Juan M.
Abstract : Graphical abstract: Highlights: An SPME/GC–MS procedure is developed for the analysis of fragrance allergens. Temperature and time are the most significant factors affecting SPME extraction. Five fragrance allergens are systematically detected in primary effluents. Four fragrances are not eliminated in the monitored sewage treatment plants. Conventional treatments based on activated sludge do not remove some allergens. Abstract: A methodology based on headspace solid phase microextraction (HS-SPME) and gas chromatography–mass spectrometry (GC–MS) determination was developed for the monitoring and evaluation of the removal efficiency of 16 common fragrance allergens and two polycyclic musks in wastewater treatment plants (WWTPs). An experimental design with a full factorial model was applied to evaluate the effects of the experimental parameters on the extraction (e.g., salt content, time and extraction temperature). After determining the optimum conditions (2.4 g NaCl, 45 min at 90 °C), an external calibration was performed and quality parameters of the proposed method were evaluated. Method detection limits in the range of 0.01–1.7 μg L −1 were obtained. Satisfactory inter-day precision values between 4% and 23% ( n = 5) were obtained for most compounds. The method was applied to the monitoring of the target analytes in samples from two WWTPs. Seven target compounds were detected at the primary effluent of both plants at μg L −1 levels. Limonene, linalool and eugenol were quantitatively eliminated during the secondary treatments of both WWTPs, while lilial, benzyl salicylate, galaxolide, and tonalide were still detected at the effluent waters.